2008
DOI: 10.1002/jgm.1283
|View full text |Cite
|
Sign up to set email alerts
|

Mouse adenovirus type 1 and human adenovirus type 5 differ in endothelial cell tropism and liver targeting

Abstract: Our data on the tropism of MAV-1 suggest that this virus may find utility in the field of gene therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…It will be of interest to determine whether MAV-1 interaction with HS-GAGs is direct or mediated by soluble factors. Recent surface plasmon resonance experiments by Lenaerts et al demonstrated that MAV-1 binds to mouse factors IX and X (35). However, the addition of factor X at physiologic concentrations did not increase the attachment of MAV-1 to mouse hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be of interest to determine whether MAV-1 interaction with HS-GAGs is direct or mediated by soluble factors. Recent surface plasmon resonance experiments by Lenaerts et al demonstrated that MAV-1 binds to mouse factors IX and X (35). However, the addition of factor X at physiologic concentrations did not increase the attachment of MAV-1 to mouse hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, mCAR mRNA is not expressed in some mouse cell lines (55) that we have found are productively infected by MAV-1 (K. R. Spindler, unpublished data). MAV-1 has recently been shown to associate with mouse coagulation factors IX and X, but this does not lead to enhanced cellular attachment to hepatocytes (35). It is not known what MAV-1 uses as attachment and/or internalization receptors.…”
mentioning
confidence: 99%
“…Interestingly, species differences in the levels of FX-mediated transduction efficacy of HAd5 mediated via heparan sulfates have been also reported for mouse and human FX (56,57). Furthermore, HAd5 and mouse adenovirus type 1 (MAd1) differ in their FX binding-dependent tropisms in the mouse model (58). While these differences do not exclude the possibility of TLR4-dependent recognition of mFXcomplexed MAd1, they imply different steric orientations of mouse FX and human FX on different capsids.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the primary attachment of MAdV-1 is independent of CAR (Lenaerts et al, 2006). Distribution of MAdV-1 to the liver is markedly lower in intravenously injected immunodeficient mice than that observed with recombinant HAdV-5 (Lenaerts et al, 2009). Moreover, MAdV-1 has been used as an oncolytic vector, proving that it is a suitable murine homolog model to test the mechanism of action of murine oncolytic AdV vectors in an immunocompetent, tumor-bearing host (Robinson et al, 2009).…”
Section: Murine Adv Vectorsmentioning
confidence: 93%
“…MAdV-1 presents mouse endothelial cell tropism (Charles et al, 1998;Kajon et al, 1998;Lenaerts et al, 2005), but it can also infect human endothelial cells (Nguyen et al, 1999) and it displays higher affinity for primary human smooth muscle cells than recombinant HAdV-5 (Lenaerts et al, 2009). MAdV-1 lacks the RGD motif in the penton base, but it contains it in the fiber knob domain (Raman et al, 2009).…”
Section: Murine Adv Vectorsmentioning
confidence: 97%